The System of Oppositions of Lithuanian Sentences with Different Intonation Patterns (Contours) - Кундротас, Гинтаутас (Kalbotyra, 1983)
The given article gives an observation of the first stage in the comparative study of intonation systems of the Russian and Lithuanian languages. The research is based on the phonological method. According to this method, a system of oppositions in Lithuanian sentences which differ in their intonation pattern is singled out. The system is compared to that in the Russian language. The aim of the research is to reveal the similarities and differences between intonation patterns in t he two languages. The intonation components in Lithuanian are singled out on the basis of the system of oppositions.